2003
DOI: 10.2172/15003646
|View full text |Cite
|
Sign up to set email alerts
|

Iron Phosphate Glass as an Alternative Waste-Form for Hanford LAW

Abstract: Although the current baseline Hanford flowsheet for immobilizing low-activity waste (LAW) assumes borosilicate-based glass, opportunities exist to improve or change this baseline to reduce the current schedule and cost requirements of accomplishing the mission of site cleanup. Development of an alternative glass-forming system can lead to this goal of cost and schedule reduction through enhanced waste loading and higher plant throughput. The purpose of this project is to investigate the ironphosphate glass sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…Mazurin et al [34] collated a wealth of data on glass formation compositions for non-silicate glasses. Glasses based on the binary system P 2 O 5 -Fe 2 O 3 have recently received attention owing to their high chemical durability and their suitability as hosts for the immobilisation of certain nuclear wastes [35][36][37][38][39][40][41][42][43][44]. Investigations of third components in these glasses include ZnO [38,39], CaO [40], Na 2 O and K 2 O [41], PbO [42] and BaO [43].…”
Section: Waste Analysis Processing Heat Treatment and Vitrificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mazurin et al [34] collated a wealth of data on glass formation compositions for non-silicate glasses. Glasses based on the binary system P 2 O 5 -Fe 2 O 3 have recently received attention owing to their high chemical durability and their suitability as hosts for the immobilisation of certain nuclear wastes [35][36][37][38][39][40][41][42][43][44]. Investigations of third components in these glasses include ZnO [38,39], CaO [40], Na 2 O and K 2 O [41], PbO [42] and BaO [43].…”
Section: Waste Analysis Processing Heat Treatment and Vitrificationmentioning
confidence: 99%
“…The formation of vitreous products may still be possible with lower P 2 O 5 equivalents, but there would be a high likelihood of crystallinity. Crystalline phases in vitrified wastes can be beneficial [26,27,[29][30][31], although recent work indicated that crystallinity in certain iron phosphate glasses loaded with inactive simulated nuclear waste can reduce the chemical durability [44]. The merits of crystallinity are dependent upon the material application.…”
Section: Waste Analysis Processing Heat Treatment and Vitrificationmentioning
confidence: 99%
“…Leco analysis indicated that about 52% of the sulfate originally present (2.9 wt%) in the waste was retained in the glasses ( Table 2). The sulfate retention in iron phosphate glasses was previously found to depend on the glass composition [8] and melting conditions such as atmosphere and temperature [13].…”
Section: Glass Formation and Physical Propertiesmentioning
confidence: 99%
“…The loading of this waste in a BS waste glass is largely determined by the allowable fraction of sulfate in the waste [4][5][6][7]. If the LAW waste loading was not limited by the sulfate content of the waste, then the amount of glass produced at Hanford could be reduced by as much as 50% [8].…”
Section: Introductionmentioning
confidence: 99%
“…A new group of phosphate glasses, iron phosphate glasses [5][6][7][8][9][10][11][12][13][14][15][16][17], known as IPG has been found to be suitable for vitrification of high level nuclear waste (HLW) rich in alkali oxides, sulphates and chrome oxides. For the same amount of waste immobilization, the density of iron phosphate vitreous waste form (3.2 g/cc) is 25% higher than that of BS waste form; consequently its volume is 25% lower than that of borosilicate waste form [9].…”
Section: Introductionmentioning
confidence: 99%